Realismo político en la guerra fría : los 50’s un periodo de mutuo miedo (2015)
ABSTRACT: Political realism was and is the theory which has governed International Relations, especially if we consider that these are dominated by a select group of nations. During the Cold War the world was divided into two, capitalist and communist sphere dictated their own rules within their respective areas of control. But as relations with its counterpart predominant fear and speculation about their strengths, weaknesses and scope. It is in these speculations (and hate) is where political realism has its scope, with its strong anthropological pessimism and constant quest for power and dominance. Both sides of the Cold War based all its international policy on the search for the total destruction of the enemy, either by weakening their economic bases or military and technological supremacy.